Thermal power plants in Turkey - Kincay, O; Ozturk, R (TAYLOR & FRANCIS INC, 2003)
The objective of this article is to investigate the status of thermal power plants (TPPs) in Turkey as of the end of 2000. Thermal resources meet approximately 60% of Turkey's total installed capacity for electric power generation, while 75% of total electricity is generated from TPPs. Of the total thermal generation, natural gas accounts for 49.2%, followed by coal for 40.65%, and 9.9% for liquid fuel. Nineteen TPPs belonging to the Turkish Electricity Generation and Transmission Cooperation (TEAS) and its affiliated partnership produce 74.6% of total electricity. Turkey's average load factor is 61%, while the net unit generation cost is 4.19 cent/kWh. The availability of low-grade lignites in the country has led to the construction of lignite fired TPPs. The use of coal, especially for power generation, is very essential to the continued economic growth of Turkey. However advanced clean coal technologies should be considered for improving the environmental performance of coal combustion.
Keywords: thermal power plants; power plants; energy utilization; environmental impact; Turkey; ENERGY; Energy & Fuels; Engineering